TECHNIQUES FOR AUTONOMOUS VOCABULARY LEARNING - NEMATULLAEVA, Muslimakhon (Journal of Research and Development, 2024)
The ability to acquire and utilize vocabulary is essential for effective communication in any language. Traditional language learning often relies on teacher-led instruction; however, autonomous vocabulary learning encourages learners to take responsibility for their own learning processes. This article is devoted to considering various techniques that facilitate independent vocabulary acquisition, thereby enhancing learners’ engagement and retention.